An Examination of Current Methodologies in Mathematics Education Through the Lenses of Purpose, Participation, and Privilege - D’Ambrosio, Beatriz Silva; Cox, Dana (Perspectivas da Educação Matemática, 2015)
In this article we reflect on our practices and begin to confront the “living contradictions” (WHITEHEAD, 1989) in our identities as researchers in mathematics education (COX et al, 2014).  From a first hand perspective we reveal and address our contradictions, organizing our discussion around the following four questions: How do we find meaning in educational research on teaching? Who is in control of the research design and who gets to participate? How should we collect and analyze data? and For what purpose do we disseminate our work? In order to best illustrate the contradictions in our work that are related to our methodological choices, we have constructed fictional dialogues that set the stage for each discussion. These dialogues capture the triggers that forced us to change the course of our research and shaped our current thinking about the ethics of conducting classroom-based research. We end this article with an invitation for readers to help define alternative research methodologies that are respectful, ethical, transformational and empowering for all participants.